Are socio-economic characteristics and maternal dietary patterns dominant factors on four-star diet achievement of infants and young children (6-23 months)? - Thiha, Kyaw; Cho, Tin Aung; Lwin, Aung (International Journal Of Community Medicine And Public Health, 2022)
Background: Nutritional deficiency is one of the challenging issues in developing countries, especially in infants and young children and maternal dietary diversity has influencing effects on children’s complementary feeding. This study aimed to assess the influence of socio-economic characteristics and dietary patterns of mothers on four-star diet achievement of infants and young children in 3 townships in Magway region as well as perceived barriers of mothers on complementary feeding practices of infants and young children. Methods: It was a cross-sectional descriptive study and mixed-method research. A total of 224 mothers were interrogated by pre-structured questionnaires. Moreover, in-depth interviews were done in 24 mothers. Results: Education level of mothers and age of the children were observed as strong predictors on children’s four-star diet achievement. In qualitative data analysis, misperceptions and lay beliefs of mothers on breastfeeding and complementary feeding practices of the children, adversities of mothers who worked outside of their home, influence of elder people in the family were identified as perceived barriers. Conclusions: This study is expected to facilitate policy makers with relevant findings and highlight that factors involved in improving the nutritional status of the infants and children.